Nanoparticles Infiltration into SOFC Cathode Backbones. (30th May 2017) - Dailly, Julian; Delrue, Aude; Ancelin, Marie; Marrony, Mathieu
Abstract : Intermediate Temperature Solid Oxide Fuel Cells (IT-SOFCs) with yttrium stabilized zirconia (YSZ) electrolyte were fabricated by the impregnation of Sm0.2 Ce0.8 O2-δ (SDC), Sm0.5 Sr0.5 CoO3-δ (SSC), CeO2, Nd1.95 NiO4+δ (NdN), Pr1.97 NiO4+δ (PrN), and La0.8 Sr0.2 MnO3 (LSM) into specific backbone cathodes: electronic conductor LSM, ionic conductor SDC and mixed ionic and electronic conductor NdN. The electrochemical performances of the symmetrical half-cells and single cells were improved using impregnated cathodes. The loading amount of the promoters have been optimized to decrease the Area Specific Resistance of the electrode (ASRelec ) and improve performance of IT-SOFCs with NdN composite cathode. The electrochemical measurements showed that a MIEC backbone is more efficient than a pure electronic or a pure ionic one. The highest ASRelec was given by LSM-impregnated sample (ASRelec = 1.15 Ω.cm 2 ) at 700 °C. At the same temperature, the lowest ASRelec was measured on a PrN impregnated into a NdN backbone (ASRelec = 0.26 Ω.cm 2 ). Complete single SOFC with and without infiltrated air electrodes have been then manufactured and the infiltration improved clearly the efficiency of the cell, more than 6% in the temperature range 650-750°C without specific optimization.